Pelaksanaan Pengecoran Saluran Peluncur Bangunan Pelimpah Bendungan Cijurey Kabupaten Bogor Provinsi Jawa Barat - Sugeng Sutikno; Teguh Imanto; Deny Ernawan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The major work of the Cijurey Dam Project Package III is located in Bogor Regency, West Java Province, which is a spillway structure consisting of iron structures and concrete structures. To achieve the right quality, on time, on cost, and zero accidents, concrete casting calculations and appropriate work implementation methods are required. This research method uses descriptive with quantitative and qualitative approaches. The stages of concrete casting work for the Cijurey Dam spillway structure's launch channel consist of preparation, measuring the launch channel block boundaries, lean concrete work, reinforcement work, formwork panel preparation, formwork panel installation, waterstop and dowel bar work, concrete sampling and slump test, concrete casting, concrete curing/maintenance, formwork dismantling, and finishing of tierod holes. The results of the study showed that the calculations for casting the concrete channel were a large volume of concrete channel casting of 135,000 m3, concrete material requirements (in the form of: 1,115,100 sacks of cement, 58,050 m3 of sand, 1,020,600 m3 of gravel, and 29,025,000 liters of water), channel formwork (surface area) of 27,675 m2, productivity of casting the concrete channel launcher of 24 m3/hour or 193 m3/day, and the efficiency of casting the concrete channel launcher time of around 125% (25% faster than planned). Meanwhile, the stages of work implementation for channel concrete casting include preparation work, measurement work for the boundaries of the launcher channel blocks, lean concrete work, reinforcement work, formwork panel preparation work, formwork lubrication work, formwork panel installation work, waterstop and dowel bar work, concrete sampling and slump test work, channel concrete casting work, concrete curing/maintenance work, formwork dismantling work, and finishing work for tierod holes. In addition, an inter-segment locking system with a shear key is used to overcome problems with the concrete pump, joint inspections are carried out during mobilization, routine inspections, repairs and replacement of the concrete pump.